Three answers to the question "what is philosophy?" : a comedy in three acts - Dalton, Stuart (Eugene, Oregon : Cascade Books, 2024)
Philosophy is like a party that started over 2,500 years ago and is still going strong. When you take a philosophy class, you're invited to join this party; but walking into a party 2,500 years late can feel a little awkward. This book is meant to solve that problem. The best way to feel welcome is to focus on how funny philosophy is, simply because its ideals are so high that humans almost never manage to reach them. This book gives three answers to the question "What is philosophy?" (1) Philosophy is a conversation that has been going on for over 2,500 years which has been full of comedy from the beginning and will continue to be funny forever if we do it right. (2) Philosophy is a very awkward business that has always been on the verge of going out of business. (3) Philosophy is something that makes almost everyone write very badly. In addition to this three-act comedy the book also contains two practical guides to being happy and successful in philosophy classes.
Includes bibliographical references and index.
Keywords: Philosophy; Philosophie; philosophy